Integrating Economics and Spiritual Perspectives: Insights from the Writings of Imam Al-Ghazali - Ghoni, Muhammad Abdul (Universitas Muhammadiyah Malang, 2026)
This paper employs qualitative content analysis as its methodological framework, focusing on the seminal works of Imam Al-Ghazali. The study examines central themes in Imam Al-Ghazali’s writings to clarify the influence of spirituality on economic thought. The findings indicate that Imam Al-Ghazali advocates for an economic system grounded in spiritual responsibility and the pursuit of both material and spiritual fulfillment. This study adopts a qualitative design to examine al-Ghazali’s primary writings on economic thought and spirituality, and the library research enabling scholars to explore the evolution of economic ideas within their intellectual and historical contexts. The results underscore the ongoing relevance of Imam Al-Ghazali’s insights in current economic discourse and highlight the importance of balancing material success with spiritual development as a solution to the problems of modern economies, which often emphasize materialism. The analysis demonstrates that integrating spiritual values into economic practices can address contemporary challenges and promote social responsibility, exemplified by mechanisms such as zakah and shadaqah, which serve as means to balance economic activity with spirituality. The results implied that dialogue between spirituality and economics, as articulated by Imam Al-Ghazali, provides a critical foundation for establishing a just and balanced society amid modern challenges.